Control of Dry-Wood Termite Infestation by Bait System - Yuliati Indrayani (Masyarakat Peneliti Kayu Indonesia, 2010)
Chemical treatments with a liquid formulation have been widely used to prevent the infestation of dry-wood termites in buildings. However, such chemical treatments are problematic due to health and the environmental considerations. Therefore, it is important to develop remedial treatments that do not pose environmental hazards. This study was conducted to develop a control strategy for dry-wood termite infestation using a bait system. Two types of experiments were designed to evaluate the performance of a bait system intended to control dry-wood termite. A gel formulation with an active ingredient (2.15% hydramethylnon) and food attractants was used for the testing (Types I and II). In the first type of experiment, Type I, the effectiveness of the bait in a small wood block specimen was evaluated. Feeding arena lumber with artificial galleries was prepared for the Type II experiment so that the response of the insects to the gel could be observed. In general, the average percentage termites that died after being exposed to the gel formulation in all two types of experiment was more than 65%, and in the gel control the average percentage of live termites was more than 75% in Type I, and more than 95% in Type II. These results suggest that the gel bait system used in this study has the potential to eliminate dry-wood termite. Further investigation will be indispensable to increase the reliability of the bait system as a control strategy for dry-wood termites.